The Euro area and the financial crisis - Beblavý, Miroslav 1977-; Cobham, David P. 1949-; Ódor, Ľudovít 1976- (Cambridge University Press, 2011)
The financial crisis of 2007–10 has presented a number of key policy challenges for those concerned with the long-term stability of the euro area. It has shown that price stability as provided by the European Central Bank is not enough to guarantee financial stability, and exposed fault lines in governance and deficiencies in the architecture of the financial supervisory and regulatory framework. This book addresses these and other issues, including why the crisis affected some countries more than others, whether the euro is still attractive for new EU states, and what policy changes and structural reforms, both macro and micro, should be undertaken to ensure its future viability. Written by a team of leading academic and central bank economists, the book also includes chapters on the cross-country incidence of the crisis, the Irish crisis and ECB monetary policy during the crisis, and studies on Spain, the Baltics, Slovakia and Slovenia
Aus der Einleitung: "This volume brings together the papers and panel contributions presented at the conference on 'The Euro Area and the Financial Crisis', held in Bratislava from 6 to 8 September 2010."
Keywords: Europäische Union; Geschichte 2007-2009; Monetary policy / European Union countries; Euro; Global Financial Crisis, 2008-2009; Finanzkrise; Währungsunion; Europäische Union. Mitgliedsstaaten; Konferenzschrift -- 2010 -- Pressburg